350 KeV Cu2+ ions induced modification in structural, morphological and electrical properties of Au doped DLC thin films. (5th April 2019) - Khan, M I; Sabir, Mudassar
Abstract: Effect of 350 KeV Copper (Cu) ions beam on the internal structure, morphology and electrical properties of gold doped diamond like carbon (Au-DLC) thin films has been discussed. RF magnetron sputtering has been used for the preparation of undoped and Au-DLC films. Au-DLC films are irradiated with Cu ions having energy 350 KeV with flounce rates 2 × 10 4, 4 × 10 4, 6 × 10 4 atoms cm −2 . Morphology, internal structure and electrical properties of these films are studied by scanning electron microscopy (SEM), Raman spectroscopy, four point probe and cyclic voltammetry (CV) techniques, respectively. Au doping and Cu ions implantation have enhanced the graphitization in DLC film. Maximum graphitization of DLC film is achieved at 4 × 10 4 atoms cm −2 flounce rate of Cu ions, according to Raman spectroscopy analysis. SEM micrographs showed that spherical like particles are present and by following agglomeration process form (Au–Cu) metal clusters on the surface of Au-DLC films. Cyclic voltammetry (CV) results indicated that Au-DLC film irradiated with 350 KeV Cu ions having 4 × 10 4 atoms cm −2 flounce rate showed low Epp and higher Ipc values; resulting high catalytic activity. Therefore, this film is good for the fabrication of counter electrode (CE) of solar cells.